Understanding the Influence of Personalized Recommendation on Purchase Intentions from a Self-Determination Perspective: Contingent upon Product Categories - Li Zhao; Bing Fu; Sha Bai (Journal of Theoretical and Applied Electronic Commerce Research)
While consumers experience shopping convenience through personalized recommendations, they are increasingly concerned about their consumption behavior being manipulated, leading to psychological resistance towards personalized recommendations. As such, research on how personalized recommendation services influence consumers’ perceptions of self-determination (which further influences their intentions to purchase) is called for. To address the gap, this current research adopts a self-determination perspective to investigate how the three basic psychological needs of self-determination (autonomy, competence, and relatedness) mediate the relationship between personalized recommendations and consumers’ purchase intentions. Moreover, this research examines whether the influence of personalized recommendations on consumers’ perceptions of self-determination is contingent upon product categories. The results of a hypothetical scenario experiments study demonstrate that competence and relatedness are critical mediators between recommendation novelty and purchase intention. The results also reveal that the impact of recommendation diversity on autonomy is contingent upon product categories, while the influence of recommendation novelty on relatedness is also contingent on product categories. This study contributes to the literature on personalized recommendations by providing an underlying mechanism for the influence of personalized recommendations on consumers’ purchase intention from the self-determination perspective, and especially by unravelling how the influence of personalized recommendations on consumers’ perceptions of self-determination is contingent upon product categories.